Social Media Success Model for Knowledge Sharing (Scale Development and Validation) - Setiawan Assegaff; Hendri Hendri; Akwan Sunoto; Herti Yani; Desy Kisbiyanti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This study aimed to evaluate the success of social media as a means of sharing knowledge among scholars in Indonesia. By using Information System Success Model (DeLone and McLean), this study develops a research model that will be used to investigate what factors are contributing to the success of social media as tool for sharing knowledge among academics. This article would focus on the discussion of instrument development and validation process. The method for development and validation the research instrument was refers to the framework proposed by McKanzie et al. This study resulted in a validated instrument, the instrument could use by researchers who are interested in study social media success for knowledge sharing.